'The Oriental Jennings': An Archival Investigation into Sir Ivor Jennings' Constitutional Legacy in South Asia. (12th March 2014) - Malagodi, Mara
Abstract This article by Mara Malagodi investigates the legacy of British constitutionalist Sir Ivor Jennings (1903–1965) in South Asia. In 1941, when Jennings moved to Sri Lanka, a new phase of prolific writing on the laws of the British Empire and Commonwealth began for him, together with a practical engagement with constitution-making experiences in decolonising nations across Asia and Africa. The archival material relating to Jennings' work on postcolonial constitutional issues forms part of the collection of Jennings' Private Papers held at the Institute of Commonwealth Studies in London. This article seeks to explain why this material has until now remained so under-researched.